DISTRIBUTION OF VELOCITIES ALONG THE SECTION OF A COHESIVE EARTHEN CHANNEL - Bobomurodov Furkat Farxod o‘g‘li; Tuychiyev Jasurbek Shokirovich; Bozorov Ma’rufjon Abdimalik o‘g‘li; Bobomurodov Fahriyor Farxod o‘g‘li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Abstract: In this article, the kinematic characteristics of water flow in connected ground channels are considered. Based on the obtained experimental data, the distribution of velocities on the channel cross-section was studied and connections were obtained.